Chinese population may require further venetoclax dose reduction beyond guidelines when combined with voriconazole: real-world evidence from China - Wang, Rongrong; Li, Yanfen; Zhang, Ran; Ren, Yuan; Liu, Yifan; Wang, Tianlin; Wu, Jin; Zheng, Xiangjin; Li, Shu; Jing, Yu (Frontiers in Pharmacology, 2025)
ObjectiveAzole antifungals inhibit the enzyme cytochrome P450 3A4 (CYP 3A4), increasing venetoclax (VEN) levels and the risk of serious adverse reactions. Dose adjustments for VEN with voriconazole (VOR) vary in studies. The drug-drug interactions (DDI), safety and economic implications of VEN with VOR in the Chinese population, who may have unique drug exposures, are unclear. This study aims to address these uncertainties and provide guidance for clinical practice.MethodsThe DDI were assessed by measuring trough (Ctrough) and peak (Cpeak) levels of VEN and concomitant azoles after ≥7 days of continuous administration. Safety and economic implications were evaluated based on the duration of cytopenias and hospitalization costs for Chinese patients with acute myeloid leukemia (AML) across three groups: VEN 400 mg, VEN 100 mg combined with posaconazole (POS) (VEN 100 mg + POS) and VEN 100 mg combined with VOR (VEN 100 mg + VOR).ResultsVOR was able to significantly increase the Ctrough (3.40 vs. 0.99, p < 0.05) μg/mL and Cpeak (3.71 vs. 2.22, p < 0.05) μg/mL of VEN 100 mg compared to VEN 400 mg alone. This increase in the plasma concentration of VEN may result in a longer duration of days to white blood cell (WBC) > 2000 cells/mm3 (25 vs. 13, p < 0.05) and a higher likelihood of increased hospitalization costs (140,469 vs. 73,513, p = 0.068) compared to VEN 400 mg alone.ConclusionChinese population may require further dose reduction of VEN beyond guideline recommendations when combined with VOR.